Acute Exposure to the Cold Pressor Stress Impairs Working Memory Functions: An Electrophysiological Study - Xin, Zengyou; Gu, Simeng; Yi, Lei; Li, Hong; Wang, Fushun (Frontiers in Psychiatry, 2020)
Stress affects cognitive functions of many psychiatry diseases, such as working memory. The results of previous literature focusing on the effects of acute stress on human working memory (WM) are equivocal. The present study explored the effects of acute stress on human WM processing using event-related potentials (ERP) techniques. Thirty healthy participants were submitted to stressful treatments and control treatment at different times. Cold pressure stress (CPS) was used as stressful treatment, while warm water was used as the control treatment before WM task. Exposure to CPS was associated with a significant increase in blood pressure and salivary cortisol. After 3-min-resting period, SBP and DBP for CPS session significantly increased relative to control treatment session (all p ≤ 0.01) and data also showed a significant increasing of 20-min-post-treatment cortisol concentration (p < 0.001) for CPS. Data of CPS session showed significantly longer reaction times, lower accuracy and K scores than that of control treatment session. Interestingly, typical difference between the two sessions was also found in N2pc and late contralateral delay activity (late CDA) components. Specifically, although non-significant main effects of treatment was found for N2pc amplitudes, there was a significant interaction between treatments and stimuli conditions ([F(2,46) = 3.872, p= 0.028, η2 p= 0.14]). As for amplitudes for late CDA, there was no interaction of treatment × condition, but a nearly significant main effect of Treatment was found (p= 0.069). The results indicated a significant negative effect of acute stress. To summarize, this study was the first using time-domain analysis of the ERPs to investigate the effects of acute stress on human WM process and reported not only performance impairments but provided high temporal resolution evidence for the detrimental effects of acute stress on processes of information encoding and maintenance.